2014
DOI: 10.1016/j.ttbdis.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Protozoan and bacterial pathogens in tick salivary glands in wild and domestic animal environments in South Africa

Abstract: A total of 7364 ticks belonging to 13 species was collected from 64 game animals (belonging to 11 species) and from 64 livestock animals (cattle and sheep) living in close vicinity at 6 localities in 3 South African Provinces (Free State, Mpumalanga, and Limpopo). The geographic distribution of all tick species was congruent with the literature except for Haemaphysalis silacea. From each infested host, a maximum of 10 males and 10 females of each tick species were dissected to isolate the salivary glands. Sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 38 publications
(60 reference statements)
1
25
0
Order By: Relevance
“…Competitive exclusion among tick-borne pathogens was observed in Algerian cattle [ 44 ]. Conversely, aggregative distribution seems to be the rule in South Africa for tick-borne pathogens monitored in mammalian blood samples or in the tick salivary glands [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Competitive exclusion among tick-borne pathogens was observed in Algerian cattle [ 44 ]. Conversely, aggregative distribution seems to be the rule in South Africa for tick-borne pathogens monitored in mammalian blood samples or in the tick salivary glands [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, Cape buffalo ( Syncerus caffer ) are known competent reservoirs for T . parva and occupies overlapping habitats with cattle, providing a continuous source of parasite for tick transmission [25,28,30]. Biological vectors that acquire infection while feeding on buffalo can transmit the pathogen to either buffalo or cattle causing significant economic loss to the livestock industry.…”
Section: Discussionmentioning
confidence: 99%
“…There are scanty reports on the ability of this species to transmit diseases in both humans and animal. However, it is a known vector agent of the protozoan Babesia bigemina, Crimean-Congo hemorrhagic fever virus (CCHFV), and Ehrlichia ruminantium [55][56][57]. Mediannikov et al [54] has reported on the ability of R. evertsi evertsi to transmit rickettsial agents in ticks that were collected in Senegal.…”
Section: Discussionmentioning
confidence: 99%